Block sparse representation approach to 2D DOA and polarisation estimation of wideband signals using a sparse vector antenna array. Issue 12 (27th October 2020) - Shi, Shuli; Xu, Yougen; Liu, Zhiwen
Abstract : In this study, a multi‐polarised two‐dimensional (2D) planar array of sparsely located vector antennas (VAs) is designed for the block sparse representation (SR)‐based 2D direction finding and polarisation parameter estimation of wideband signals. In order to alleviate the inter‐VA mutual coupling effect, the minimum inter‐VA spacing of the 2D sparse array is constrained to be no less than one wavelength that corresponds to the highest signal frequency. To reduce the computational complexity of parameter estimation, the 2D block SR model for the 2D difference coarray output at a certain frequency bin is established, under which the two direction cosine terms for 2D direction‐of‐arrival (DOA) estimation are decoupled with the polarimetric terms. This enables separated but simultaneous 2D direction finding and polarisation parameter estimation with the newly developed joint 2D block orthogonal matching pursuit (Joint‐2D‐BOMP) subband fused sparse recovery algorithm. Moreover, with the use of two spatial only (polarisation independent) over‐complete dictionaries, the representation dimension of the new 2D block SR model is greatly reduced as compared with the traditional space‐polarisation joint SR model. The efficacy of the presented VA array geometry and the associated parameter estimation method is validated by computer simulations.